Post Traumatic Growth pada Korban Broken Home - Intan Mawadatur Rohmah; Hesty Yuliasari (Jurnal Ilmiah Psikologi MIND SET, 2023)
Post-traumatic growth refers to the positive growth experience after experiencing trauma, such as increased wisdom, maturity, appreciation for life, and spiritual growth. Meanwhile, broken home refers to a family in a disordered condition, with both parents no longer living together in one household or having already divorced, resulting in children usually living with a single parent. This study used a qualitative method with a phenomenological approach, and involved four research subjects who were children of broken homes from families who had divorced. The subjects were males and females aged 20 to 27, selected using purposive sampling. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of analysis technique. The results of the study showed that all four subjects were able to achieve post-traumatic growth.